Terceiros anos do Ensino Fundamental: castelos de areia da sala de aula - Cruz, Alexandre José (2016)
This research arose from an inquietude originating with a reflection on the results of master’s research by the author about the use of technology in schools. During that study, it was possible to verify the difficulty of early elementary teachers when proposing tasks for students to carry out using donated computers. As such, questions arose along with a desire to comprehend how teachers organize activities to be used in the classroom, how teachers structure the classes, and what kind of educational experiences they provide students. We opted to study third grade classrooms since they are considered to be a privileged locus for understanding and explaining the teaching environment. The point of departure was always the teachers, but the strategic position this grade has occupied over the last decade, in the organization of instruction throughout the schooling process, was considered. For this reason, we initially counted on the ample spectrum of studies and research realized in recent decades. As such, the central objective of this research was to characterize the fundamental aspects of the work of two third grade teachers and their classrooms in two different schools in a small, rural city in the state of São Paulo. This city was chosen since it is understood that the relations is these spaces are very different from those in medium-sized and large cities, locations where educational research is already happening regularly. In addition to an analysis of the official documents of these schools, classroom observations were carried out between the months of March and October of 2014. Procedures for classroom observations, data collection and analysis were based on Gimeno (2000) who, with his concept of “the architecture of practice,” suggests essential points for observing teaching practice in the classroom. This allows us to understand the characteristics of the class and classroom practices through the educational tasks proposed for the students, possible points to consider as a fundamental part of this concept. In order to amplify the qualitative dimension of this understanding, we also made use of Bloom (1974) and his collaborators’ concept of taxonomy, since in addition to classifying the educational tasks, cognitive levels were highlighted, from simple to elaborate levels of thinking. This research indicated that even when faced with different teacher profiles, uneven educational objectives among the schools, and educational tasks that could be characterized as unequal, the students advanced little in their cognitive levels, with teaching and learning designs defining a three-tiered construction marked by three levels of results and the formation of three groups of students in regards to their learning outcomes